Sex of Natural Person in Private International Law: Historical Evolution and Normative Response (Part I) - Hernández Rodríguez, Aurora (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This paper will try to analyze how and to what extent private international law has given normative response and methodological treatment to sex and, where appropriate, gender of the natural person throughout its history, considering the conception of sex prevailing in each era and its evolution from a single sex system (male) to a binary system: sex-gender (male/female/feminine/masculine). Issues such as: the legal status of women, and its consideration by private international law, Mancini’s theory of the personality of laws and with it the loss of nationality of married women; the reaction and struggle of the feminist movement at national and international level against this principle or the great challenge that the slow but steady advance of the principle of legal equality and its incorporation into the conflict of law represented for the private international law doctrine, will be the object of special attention.